Environmental Ethics for Upward Bound Math-Science Program - Denney, Anne; Wigfall, LaBarbara James; Lester, Erica (Kansas State University, 2010)
Professor Wigfall developed an environmental science experience for Upward Bound students between 7th and 12th grade from Topeka, KS. This summer 6- week course required students to understand the interrelationships of the natural world, identify and analyze environmental problems both natural and man-made, and examine alternative solutions for resolving and/or preventing them. KSU partnered with the students who explored six themes through class assignments, video, internet searches, field trips to Konza Prairie, student farm/ Derby Composting project, greenhouses, and herbarium. The course included: 1) weekly service at the KSU recycling center; 2) daily accounting of personal waste and recycling; 3) maintenance of their terrariums made from recycled bottles; 4) composting and planting; 5) reuse of liquor bottles discarded by local bars; and 6) measuring of creek flow on the prairie. Students extended their recycling projects to their families in Topeka on the weekends in order to raise awareness.